Metabolomic Analysis, Fast Isolation of Phenolic Compounds, and Evaluation of Biological Activities of the Bark From Weinmannia trichosperma Cav. (Cunoniaceae) - Barrientos, Ruth; Fernández-Galleguillos, Carlos; Pastene, Edgar; Simirgiotis, Mario; Romero-Parra, Javier; Ahmed, Shakeel; Echeverría, Javier (Frontiers in Pharmacology, 2020)
The endemic species Weinmannia trichosperma (local name: Tineo; Mapuche name: Müdehue) is used in traditional Mapuche medicine in the treatment of chronic diarrhea, the prevention of some types of cancer, inflammation and wound healing. This study focused on the isolation, analysis, and characterization of the biological activity of compounds and medicinal extracts from Tineo bark for the first time. The edible infusion and tincture of the bark was characterized regarding antioxidant and important enzyme inhibitory activities, phenolics and flavonoids content and UHPLC-ESI-OT-MS metabolite profiling. Twenty-five metabolites were detected in the medicinal infusion of W. trichosperma, while the major four compounds were rapidly purified, with a CPC countercurrent separation device, and were quantified in the bark using a validated analytical HPLC methodology. The antioxidant properties were measured by ORAC, DPPH, TEAC, and FRAP methods. The infusion displayed a strong DPPH and ABTS scavenging activity (IC50 = 20.58 µg/mL and 3.070 µg/mL, respectively) while a moderated effect was observed in the FRAP, ORAC and ABTS assays. The infusion showed a content of phenolic and flavonoid compounds of 442.1 mg GAE/g and 15.54 mg QE/g respectively. Furthermore, the infusion showed a good and promissory inhibitory activity (33.80, 33.12 and 82.86 % for AChE, BuChE and, 5-hLOX respectively) and isoastilbin (51.70, 50.10, and 34.29-80.71 % for AChE, BuChE and, 5-hLOX respectively). The biomolecules identified in this study support the traditional uses of this bark and the potential industrial interest from this Valdivian plant species.